New Data on the Chalcolithic and Bronze Age Periods in the South-Eastern Greater Periphery of the Jazmurian Basin: Archaeological Survey Along the Sarbaz Valley and in Adjacent Areas in Iranian Baluchestan. Issue 1 (2nd January 2020) - Sarhaddi-Dadian, Hossein; Mutin, Benjamin; Moradi, Hossein
ABSTRACT: This article reports results from an archaeological survey conducted along the Sarbaz Valley and in adjacent areas in parts of Sarbaz and Chahbahar counties in the Sistan and Baluchestan province of south-eastern Iran. The surveyed area is located in the south-eastern greater periphery of the Jazmurian Basin, in-between the Bampur Valley ca. 120 km. to the north-west and the Kech-Makran region less than 100 km. to the south-east in Pakistan. Both these two regions were investigated in the past and yielded abundant archaeological records dating to the Chalcolithic and Bronze Age periods. It was particularly interesting to explore the area considered in this article to understand how it connected with these two archaeologically-rich neighbouring regions during these periods. From a broader perspective, this survey also aimed to contribute to the reconstruction of the ancient cultural spheres – the location of their spatial boundaries and intra- and inter-regional interaction routes – in the south-easternmost territories of the Iranian Plateau. As a result, twenty sites dating to the Chalcolithic and/or Bronze Age periods were found. These sites and their surface materials are here presented and discussed with reference to the broader context of these periods in these territories.